2020
DOI: 10.1016/j.eclinm.2020.100477
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional vulnerability of people with disability to HIV infection: Results from the handiSSR study in Bujumbura, Burundi

Abstract: Background In resource-limited contexts, available data indicate that people with disability are disproportionally affected by the HIV epidemic. While disability resulting from chronic HIV infection has received some attention, few epidemiologic studies have examined the vulnerability of people with disability to HIV acquisition. The aims of the study were as follows: to estimate and compare HIV prevalence among people with and without disability living in Bujumbura, Burundi; to examine how the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
0
21
1
Order By: Relevance
“…The latest Lancet HIV paper by Pierre De Beaudrap and colleagues illustrates why we need disability-focused research to address vulnerabilities of those who have been left behind in the response to HIV and AIDS [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latest Lancet HIV paper by Pierre De Beaudrap and colleagues illustrates why we need disability-focused research to address vulnerabilities of those who have been left behind in the response to HIV and AIDS [1].…”
mentioning
confidence: 99%
“…However, in past, cross-sectional, surveys it was difficult to distinguish between women who were living with HIV and acquired disability and those women who grew up with disability and were later infected with HIV [2,3]. The methodology developed by de Beaudrap et al distinguishes between people with 'early and late disability onset' and therefore allows us to identify HIV prevalence and risk factors among people who grew up with disability ('early disability') [1]. The data shows that the prevalence of HIV is higher among women with disabilities then their peers without disabilities or men.…”
mentioning
confidence: 99%
“…In a similar vein, other research has found that men with disabilities are less likely to report engaging in sexual risk behaviours, such as multiple concurrent partners [ 56 ]. Indeed research on HIV and disability has revealed that women with disabilities are at particular risk of exposure to HIV because of their exposure to sexual violence, exploitation and transactional sexual activities [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this study we used data collected through two cross-sectional studies conducted in Yaoundé, Cameroon between 2 October 2014 and 30 November 2015 (the HandiVIH study [ 12 ]) and in Bujumbura, Burundi between 20 December 2017 and 20 December 2018 (the HandiSSR study [ 13 ]). These surveys were part of a series of studies conducted on the burden of HIV infection among people with disabilities in sub-Saharan Africa.…”
Section: Methodsmentioning
confidence: 99%